(untitled) (Saúde Ética & Justiça, 2015)
The aim of this study was to analyze the morbidity profile of the government supported disability insurance beneficiaries in the city of Erechim, RS, through the data obtained from the government social security database for the voluntarily insured and mandatorily insured (employees and non-employees), in the first half of 2015. Data analysis indicated that the three groups differed regarding gender, the average age of having the benefit granted and contribution period. The voluntarily insured mostly were elderly females older than fifty years of age who had contributed for a shorter period when the benefit was granted. The most frequently found diseases according to the ICD-10 Chapters were those of the musculoskeletal system (XIII), followed by trauma injuries (XIX) and mental disorders (V), with significantly distinguished morbidity profiles among groups. When comparing the frequency of the disability insurance granted for each group of disease per group of beneficiaries, the voluntary insured group had a higher frequency of circulatory diseases (IX); the employee group, a higher frequency of aids due to mental disorders (V), and, the non-employee mandatory insured, due to injuries from external causes (XIX).